A Brief Review of Effective Teaching Practices That Maximize Student Engagement - Harbour, Kristin E.; Evanovich, Lauren L.; Sweigart, Chris A.; Hughes, Lindsay E. (Preventing School Failure: Alternative Education for Children and Youth, 2015)
What teachers do and how students perform intersect, making teachers a critical factor for determining student success. When teachers use effective practices, they maximize the probability that students will be actively engaged in instruction. Student engagement is one of the most well-established predictors of achievement; when students are more engaged in academic instruction, they tend to have greater academic and social success. This article aims to review empirical literature in support of three evidence-based practices for maximizing student success. These practices include modeling desired academic and social behavior, providing opportunities to respond to curricular content, and providing academic and behavioral feedback.